The World Series - Duden, Jane. (New York : Crestwood House ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1992)
Surveys the notable events in the history of the annual baseball playoffs between the National and American Leagues.
Keywords: Baseball -- History